ANALISIS KETERPILIHAN ACHMAD YUSUF RONI SEBAGAI CALON ANGGOTA DPRD KABUPATEN KUDUS DARI PDI PERJUANGAN DALAM PEMILIHAN LEGISLATIF 2014 - Dimas Anom Nugraha; Susilo Utomo; Lusia Astrika (Journal of Politic and Government Studies, 2016)
ABSTRACT Achmad Yusuf Roni was one of the candidates for members of DPRD Kabupaten Kudus legislative elections in 2014 were derived from the PDI Perjuangan . Electoral district (Dapil) for Achmad Yusuf Roni was Dapil IV, which includes Kecamatan Dawe and Kecamatan Jekulo in Kudus. Mannered known figure in the community and who are loyal to a political party which he joined, Achmad Yusuf Roni is pure cadre from the PDI Perjuangan Kabupaten Kudus. Structurally, Achmad Yusuf Roni was the Secretary of the Branch Council (DPC) PDI Perjuangan Kudus for the period 2010 to 2015. With a relatively young age, which is 31 years old in 2014, Yusuf Achmad get ordinal number 1 (one). The ordinal number of 1 that is identical to prospective members DPRD is expected to be won an election. This study has revealed what are the main factors that determine victory Achmad Yusuf Roni. With the vote total of 5,030 votes, the highest compared to other candidates who also came from the PDI Perjuangan and the same electoral district (Dapil). Victory of Achmad Yusuf Roni affected by his popularity in the middle of the voters and the role of Musthofa. Musthofa is the Chairman of PDI Perjuangan Kudus, and Regent of Kudus. With the support of Mustafa, the party's political machine was geared to help Achmad Yusuf Roni in this contestation. In accordance with the purpose of PDI Perjuangan Kudus, Achmad Yusuf Roni managed to get one seat in parliament Kudus. Although the vote gained much from the original target planned. Overall PDI-P was able to obtain 9 seats out of 45 seats in DPRD Kudus. Keywords : Electability, PDI Perjuangan, the legislative elections